Concept of curriculum evaluation in Education Program of Electrical Engineering using AUN-QA as benchmarking - Dolly, Vice Pramutia; Mukhaiyar, Riki (Jurnal Pendidikan Teknologi Kejuruan, 2020)
Qualified graduates is supported by an efficient process of education, improvement of competence on an ongoing basis, and appropriate curriculum. The curriculum becomes an important part in education. Each educational institution graduates expect superior quality, good morals, knowledge and competence of skilled labor. Quality of qualified graduates will increase the demand of stakeholders to recruit workers in the industry related. It is necessary to implement a quality program in an effort to provide the best service for educational activities. This study discusses the program carried out by educational and vocational study program in electrical engineering (EEVE) achieve the goal to do assessment by AUN-QA (ASEAN University Network-Quality Assurance) in evaluating the curriculum. AUN-QA aims to conduct quality assurance of courses that a member of AUN, as well as guiding and guide the university to improve and maintain the quality of the university. Researchers use qualitative research using the comparative method of ex-postfacto with the kind of correlational study. The study was conducted with data collection, such as observation, interviews, field observation and documentation study. This research resulted in the development of curriculum in vocational and educational courses in electrical engineering (EEVE), in terms of meeting the basic needs for qualified graduates, competent and professional in accordance with the standards of the AUN-QA. Through this research is expected to be a pattern for other courses to evaluate the curriculum for graduates scored an excellent, competent and qualified